Aggression in Acute Inpatient Psychiatric Care: A Survey of Staff Attitudes. Issue 3 (September 2019) - Ezeobele, Ifeoma E.; McBride, Rachel; Engstrom, Allison; Lane, Scott D.
Introduction: Inpatient aggression poses consistent complications for psychiatric hospitals. It can affect patient and staff safety, morale, and quality of care. Research on staff attitudes toward patient aggression is sparse. Purpose: The study explored staff attitudes toward patient aggression by hospital position types and years of experience in a psychiatric hospital. We predicted that staff experiencing patient aggression would be related to working in less trained positions, having less psychiatric work experience, and demonstrating attitudes that were consistent with attributes internal to the patient and not external. Methods: Fifty-one percent completed online survey using Management of Aggression and Violence Attitude Scale, along with demographics, years of work experience, and number of times staff experienced aggressive event. Results: Management of Aggression and Violence Attitude Scale scores, staff position types, and years of experience were related to the number of aggressive interactions. Nurses and psychiatric technicians reported highest number of exposures to patient aggression, followed by physicians; however, support staff reported less patient aggression. More years worked in a psychiatric hospital was associated with more aggressive experience. Conclusion: Nurses, psychiatric technicians, and physicians reported greater exposure to patients' aggression than support staff. Training programs, developed specifically to individual position types, focusing on recognition of sources of aggression, integrated into staff training, might reduce patient on staff aggression in psychiatric hospitals.